Target detection in forward scattering radar - Mohamed, Mohamed Khalaf Alla Hassan; Raja Abdullah, Raja Syamsul Azmir; A. Rasid, Mohd Fadlee (Universiti Putra Malaysia Press, 2009)
This paper analyses electromagnetic signal scattered from the target crossing the Forward Scattering Radar (FSR) system baseline. The aim of the analysis was to extract the Doppler signal of a target under the influence of high ground clutter and noise interference. The extraction was used for the automatic target detection (ATD) in the FSR system. Two extraction methods, namely Hilbert Transform and Wavelet Technique, were analyzed. The detection using the Hilbert Transform is only applicable for some conditions; however, the detection using the Wavelet Technique is more robust to any clutter and noise level. From 55 sets of signal, only 4% of false alarm was detected or occurred when the Wavelet Technique was applied as a detection scheme. Two sets of field experimentation were carried out and the target's signal under the influence of high clutter had successfully been detected using the proposed method.